Design of flying mechanism of a Micromechanical Flying Insects (MFI) / Ahmad Akmal Abdul Aziz - Abdul Aziz, Ahmad Akmal (2017)
Micromechanical flying insects (MFI) is a miniature aerial unmanned vehicle (UAV) composed of body, wings and control system to operate the mechanism. Studies have been developed since 1998 in the University of California, Berkeley, USA to produce biomimetic robotic insects. Interpreting these prior studies has lead to a new design idea that will improve the mass, size and linkages system. This study focuses on the flying mechanism component of the MFI and also to select the most suitable design before producing the prototype. Three different designs with different mechanisms were proposed. Morphological chart analysis is used to determine the best mechanism based on few parameters. Mass, size, material and linkages are the substantially important consideration for the design. Solidworks software is used to analyze these designs. Mechanism 3 is chosen as the best design for the study with a total wingspan of 25.62 cm. Mass of the mechanism is 0.062 kg and the material used for the prototype is ABS. Two types of different size of binary links were chosen as the linkages system. Consideration on manufacturing the prototype also has taken to make sure dimension for each parts of the mechanism is capable to fabricate.